Answer:
k = -9
Step-by-step explanation:
f(x) = 2x²+kx-20
From remainder theorem,
x = 10 and f(10) = 90
f(10) = 90
Subsitute the value of x into the expression above.
f(10) = 2(10²)+10k-20 = 90
200+10k-20 = 90
Solve for k by collecting like terms
10 k = 90+20-200
10k = 110-200
10k = -90
k = -90/10
k = -9.
Hence the value of the constant is -9
Answer:
I'm pretty sure it's a
Step-by-step explanation:
A:41
B:27
C:38
D:40
Answer:
she can purchase 5 cheesecakes
Step-by-step explanation:
15.99*5=79.95
if we add 9.99 for the shipping of thw whole order
79.95+9.99=89.94
Answer: x=3
Step-by-step explanation:
To find the zeros, you want to first factor the expression.
x³+x²-36
(x-3)(x²+4x+12)
Now that we have found the factors, we set each to 0.
x-3=0
x=3
Since x²+4x+12 cannot be factored, we can forget about this part.
Therefore, the zeros are x=3. You can check this by plugging the expression into a graphing calculator to see the zeros.